Fatal bronchopneumonia caused by skunk adenovirus 1 in an African pygmy hedgehog. (January 2019) - Needle, David B.; Selig, Martin K.; Jackson, Kenneth A.; Delwart, Eric; Tighe, Ellyn; Leib, Stephen L.; Seuberlich, Torsten; Pesavento, Patricia A.
Eleven adult African pygmy hedgehogs ( Atelerix albiventris ) were added to a group of 35 animals, and within 10 d, respiratory distress affected 8 of 35 resident animals in the group, but none of the introduced animals. Three animals died following onset of clinical signs. Tissues from one animal were collected and submitted for histopathology, which revealed acute necrotizing bronchopneumonia and tracheitis with intraepithelial intranuclear inclusion bodies. Electron microscopy identified 75–90 nm diameter encapsulated icosahedral virions. Degenerate nested PCR analysis identified adenovirus within the affected lung tissue. Deep sequencing showed 100% homology to skunk adenovirus 1 (SkAdV-1). Adenoviruses are usually species-adapted and -specific, but our case supports the single previous report of non-skunk infection with SkAdV-1, indicating that this virus can infect other species, and further shows that it can cause fatal disease.